A phylum-wide survey reveals multiple independent gains of head regeneration in nemertea - Zattara, Eduardo Enrique (2019)
Animals vary widely in their ability to regenerate, suggesting that regenerative ability has a rich evolutionary history. However, our understanding of this history remains limited because regenerative ability has only been evaluated in a tiny fraction of species. Available comparative regeneration studies have identified losses of regenerative ability, yet clear documentation of gains is lacking. We assessed ability to regenerate heads and tails either through our own experiments or from literature reports for 35 species of Nemertea spanning the diversity of the phylum, including representatives of 10 families and all three orders. We generated a phylogenetic framework using sequence data to reconstruct the evolutionary history of head and tail regenerative ability across the phylum and found that all evaluated species can remake a posterior end but surprisingly few could regenerate a complete head. Our analysis reconstructs a nemertean ancestor unable to regenerate a head and indicates independent gains of head regenerative ability in at least four separate lineages, with one of these gains taking place as recently as the last 10-15 Myr. Our study highlights nemerteans as a valuable group for studying evolution of regeneration and identifying mechanisms associated with repeated gains of regenerative ability.